An Event Mesh for Event Driven IoT Applications. - Berjón, Roberto; Mateos, Montserrat; Beato, M. Encarnación; Fermoso García, Ana (International Journal of Interactive Multimedia and Artificial Intelligence, 2022)
In IoT contexts, software solutions are required to have components located in different environments: mobile, edge, fog or cloud. To design this type of application, event driven architecture (EDA) is used to develop distributed, scalable, decoupled, desynchronized and real-time components. The interconnection between the different components is done through event brokers that allow communication based on messages (events). Although the design of the components is independent of the environment in which they are deployed, this environment can determine the infrastructure to be used, for example the event brokers, so it is common to have to make modifications to the applications to adapt them to these environments, which complicates their design and maintenance. It is therefore necessary to have an event mesh that allows the connection between event brokers to simplify the development of applications. This paper presents the SCIFI-II system, an event mesh that allows the distribution of events between event brokers. Its use will allow the design of components decoupling them from the event brokers, which will facilitate their deployment in any environment.